(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
This study evaluated the chemical property and effect of Elaeis guineensis kernel (EGK) oil on calcium ion-induced mitochondrial membrane permeability transition (MMPT) using standard in vitro methods. Results showed the EGK oil values for iodine (46.53±1.8 Wij’s), saponification (246.33±1.2 mgKOH/g), acid (10.32±2.5%) and peroxide (3.03±0.4 mEq/kg). EGK oil (150 µg/ml) exhibited a maximal inhibitory (80.9±4.8%) effect on MMPT. Furthermore, EGK oil (100 µg/ml) maximally stabilized (96.72±5.2%) erythrocyte membrane against hypotonicity-induced hemolysis. In addition, EGK oil (250 µg/ml) inhibited heat-induced protein denaturation by 12.42±2.6% and mitochondria lipid peroxidation by 61.03±3.7%. This study showed that EGK oil could possess mitochondria protective agent(s).